IMPROVING PROFITABILITY OF INTEGRATED RICE-SHRIMP FARMING IN BRACKISH AREA: A CASE STUDY OF MEKONG DELTA, VIETNAM - Vo, Ha Van; Di, Huynh Ba; Phuoc, Nguyen Van (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2023)
Rotation between rice and shrimp farming by way of filter ponds and diversification of farm activities was studied with the aims of testing the efficiency of filter ponds and evaluating the combination of incorporating the growing of upland-crops on dikes of rice fields. Three groups of farmers participated in study trials which were the pilot group used a filter pond and applied new methods, the control group had a filter pond and applied the recommended new methods, and the normal practice (control) group not having a filter pond. Results showed that the rice-shrimp farming system using a filter pond improved water quality (pH, alkalinity and salinity) and reduced input costs. Growing upland crops on the dikes had a high financial return; though for both vegetables and the grass for the dairy cows will strongly depend on the market. On one hectare of land, farmers using a filter pond for rice-shrimp farming combined with upland-crops had a higher economic return than the traditional rice-shrimp farming system (2,812 compared with 854 USD/ha/year). However, implementing this model requires farmers to build filter ponds to aid freshwater storage, proper management skills and family labour resources. Diversification of farm activities such as integrated rice-shrimp culture may be a strategy for farmers for adapting to the impacts of climate change such as extreme weather events, less rain and saltwater intrusion.